The evaluation of oral competence in second languages. The case of English in the professional environment - Pomposo Yanes, Mª Lourdes (Didáctica. Lengua y Literatura, 2016)
The evaluation of the oral competence is one of the most subjective ones in second language teaching and sometimes the most conflictive one related to the fair or unfair testing depending on the aims of that evaluation. Apart from the subjectivity problem we have to add the difficulty of the required time consuming fact, mainly if that evaluation is carried out in an individual way, the activity preparation, the right rubric and all the requirements that a good evaluation process or protocol implies. In this document we will display a theoretical framework of evaluation of oral competence in second language acquisition, the evaluation process, the importance of rating scales and their descriptors studying the most commonly used in well-known institutions and we present a holistic rate scale to be presumably used in the process of candidates selection in a job interview.